2022
DOI: 10.30574/wjarr.2022.14.2.0217
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting adherence to meat hygiene practices of beef butcheries in Kasangati Town Council, Wakiso District, Uganda

Abstract: Poor meat hygiene practices are a major cause of food borne diseases which has led to morbidity and mortality globally. The World Health Organization estimates that over 600 million foodborne illnesses and 420 million deaths worldwide are due to poor hygiene practices in the meat sector, with the developing countries carrying the brunt of this load. The situation in Uganda is not much different from the global statistics and many studies have been undertaken especially in the capital city Kampala on butcher hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, in Uganda, a study reported that only 38% of butcheries were managed by owners, while 61.2% were managed by employees (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, in Uganda, a study reported that only 38% of butcheries were managed by owners, while 61.2% were managed by employees (22).…”
Section: Discussionmentioning
confidence: 99%